GR-FB block cleaning scheme in flash memory. - Abd.Rahiman, Amir Rizaan; Mansor, Noridayu; Abdul Halin, Alfian; Putra Sumari,; Kamarulhaili, Hailiza (2011)
Flash memory is a non-volatitle memory that offers several superior advantages as a data storage device in many electronic gadgets. However its two operational characteristics, namely 1) Out-place updating and 2) Cleaning process will affect its performance as an efficient storage sub-system if not managed wisely. This paper proposes a new block cleaning scheme, called Greedy and Frequency-based (GR-FB). The scheme combines the victim block selection procedure and the valid-data re-organizing procedure to improve the block cleaning process performance. The trace-driven simulations have shown the GR-FB scheme performs better than existing cleaning process schemes where the cleaning cost is reduced at least by 8% and the wear-leveling level for all blocks in the memory array are nearly equal.